2020
DOI: 10.1071/mf18392
|View full text |Cite
|
Sign up to set email alerts
|

Mitigating a global expansion of toxic cyanobacterial blooms: confounding effects and challenges posed by climate change

Abstract: Managing and mitigating the global expansion of toxic cyanobacterial harmful algal blooms (CyanoHABs) is a major challenge facing researchers and water resource managers. Various approaches, including nutrient load reduction, artificial mixing and flushing, omnivorous fish removal, algaecide applications and sediment dredging, have been used to reduce bloom occurrences. However, managers now face the additional challenge of having to address the effects of climate change on watershed hydrological and nutrient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(47 citation statements)
references
References 97 publications
(144 reference statements)
1
45
1
Order By: Relevance
“…It is indisputable that both R. raciborskii and M. aeruginosa are highly successful and invasive species. Several factors may favour their dominance in aquatic ecosystems and their global occurrence, such as anthropogenic nutrient loading, rising temperatures, rising salinity, increased atmospheric levels of CO 2 , enhanced vertical stratification, increased water residence time and more extreme climatic conditions (Mantzouki et al, ; Paerl et al, ). Specific traits of these two species are also involved in their ecological success, such as buoyancy provided by gas vesicles, which allows them to access optimum light and nutrient conditions in the water column; ability to release toxins; formation of akinetes in R. raciborskii and tolerance to a wide range of light intensities.…”
Section: Discussionmentioning
confidence: 99%
“…It is indisputable that both R. raciborskii and M. aeruginosa are highly successful and invasive species. Several factors may favour their dominance in aquatic ecosystems and their global occurrence, such as anthropogenic nutrient loading, rising temperatures, rising salinity, increased atmospheric levels of CO 2 , enhanced vertical stratification, increased water residence time and more extreme climatic conditions (Mantzouki et al, ; Paerl et al, ). Specific traits of these two species are also involved in their ecological success, such as buoyancy provided by gas vesicles, which allows them to access optimum light and nutrient conditions in the water column; ability to release toxins; formation of akinetes in R. raciborskii and tolerance to a wide range of light intensities.…”
Section: Discussionmentioning
confidence: 99%
“…These studies have reported that increased pulses of nutrient loading, along with wind-induced nutrient resuspension from the sediments, may ultimately stimulate HABs and amplify preexisting eutrophication (James et al, 2008;Zhu et al, 2014). The HAB in the LO and SLE region in 2018 was one of the largest recorded and may have been related to rainfall and high winds from Hurricane Irma and heavy rainfall in spring 2018 (Paerl et al, 2019). Our short-term lake and estuary responses to Hurricane Irma emphasize that studies focusing on both short and long-term effects are necessary for understanding hurricane impacts on shallow, eutrophic ecosystems and cyanoHAB dynamics.…”
Section: Hurricane Irmamentioning
confidence: 99%
“…Cyanobacterial blooms are changing in relation to climate change (Paerl et al 2020). By using new and diverse scientific tools, various temporal and spatial scales of monitoring and detection of cyanobacterial blooms will be important to water resource managers.…”
Section: New Ways Of Monitoring For Cyanobacteriamentioning
confidence: 99%
“…Approaches to manage blooms have included reductions in nutrients to inland and coastal waters to limit the biomass of cyanobacteria (Willén 2001;Jeppesen et al 2005); artificial mixing to prevent thermal stratification in lakes and reservoirs (Visser et al 2016); flow management to reduce thermal stratification in rivers (Mitrovic et al 2003(Mitrovic et al , 2011; food web manipulation to increase the grazing of cyanobacteria (Mehner et al 2002) and macrophyte recovery to promote clear water states through allelopathy (Song et al 2019), among other techniques. Paerl et al (2020) discuss the confounding effects and challenges posed by climate change on toxic cyanobacterial blooms. Paerl et al (2020) suggest that rising temperatures and the increasing frequencies and magnitudes of extreme weather events will promote cyanobacterial blooms and affect the efficacy of remedial measures, and suggest the setting of stricter nutrient reduction targets for bloom control.…”
Section: Management and Mitigation Of Bloomsmentioning
confidence: 99%
See 1 more Smart Citation